"Where there's a will …": Reforming postsecondary education in Canada's and the European Union's decentralized systems. (22nd May 2013) - Haskel, Barbara
Abstract The Bologna Process that created the European Higher Education Area is an elaborate open method of coordination (OMC)‐type process involving the member states, interested parties, social partners and experts. It is the product of the incentives of the actors who created and who sustain it; it embodies a purpose. Is such a process relevant for policy making on postsecondary education in the Canadian federal system? One would need to know if there is a compelling vision, objective or anxiety that motivates the key actors.